Aromatic polyesters derived from 5, 5′-disubstituted bis(m-phenylene) crown ethers. (25th April 2018) - Gibson, Harry W.; Nagvekar, Devdatt S.; Yamaguchi, Norimitsu; Delaviz, Yadollah; Jones, Jason W.; Balanda, Peter; Prasad, Abaneshwar; Marand, Herve'
Abstract: A new monomer of the AB type, 5-carboxy-1, 3-phenylene-5′-hydroxy-1′, 3′-phenylene-32-crown-10 (5 ), was synthesized. Direct polymerizations of bis(5-hydroxy-1, 3-phenylene)-32-crown-10 (13 ), an AA diphenolic macrocyclic monomer, with BB diacid monomer bis(5-carboxy-1, 3-phenylene)-26-crown-8 (14 ) and its larger analog bis(5-carboxy-1, 3-phenylene)-32-crown-10 (16 ) were accomplished via the Higashi method. The resultant polyesters 15 and 17, which both contain two macrocycles per repeat unit, were soluble in common organic solvents such as chloroform and tetrahydrofuran, amorphous in nature and possessed high thermal stability (5% weight loss > 370 °C in air). Main chain poly(ester crown ether)s 18 and 19 based on bis(5-carboxy-1, 3-phenylene)-32-crown-10 (16 ), and hydroquinone (HQ) and biphenol (BP), respectively, were synthesized; these two polyesters also possess high thermal stability (5% weight loss > 386 °C in air) and are amorphous. These polymacrocycles are suitable polytopic hosts for complexation with 4, 4′-bipyridinium derivatives, as demonstrated by the binding of paraquat diol (21a ) by polyester 20 with Ka = 2.0 (±0.7) x 10 2 M −1 (23 °C, 4:6 w:w CD3 CN:CDCl3 ). Threading of the cyclic units in these polyesters by linear polymers such as polystyrene and PMMA leads to compatiblized blends via polypseudorotaxane formation; this methodology represents a new approach to compatibilization. Graphical abstract: Image 1 Highlights: 5-Carboxy-1, 3-phenylene-5′-hydroxy-1′, 3′-phenylene-32-crown-10 prepared. Polyesters prepared from a 32-membered bisphenol and 26- and 32-membered diacids. Polyesters prepared from 32-membered diacid with hydroquinone and biphenol. All the polyesters were amorphous with high thermal stability. Threading these polyesters by polystyrene and PMMA leads to compatiblized blends.